UFR ( UNDER FREQUENCY RELAY ) RELAY ANALYSIS IN OVERCOMING BLACK OUT NIAS ISLAND - Andi Hernawan; Siti Anisah; Hamdani (INFOKUM, 2022)
The power system disturbance that occurred at the Nias power plant due to overcurrent caused a trip to the Nias Gas Engine Power Plant (PLTMG) generator. This causes a decrease in frequency due to the system losing power supply. Frequency interference can be detected automatically with UFR (Under Frequency Relay). The working principle of UFR is to compare the value of the frequency system and the value of the frequency setting which determines the amount of load removed. This study analyzes the performance of UFR on the Nias island power system by simulating a decrease in UFR resulting in a decreased frequency system state.